BIOGAS SEBAGAI PENGGANTI MINYAK TANAH DAN KAYU BAKAR UNTUK BAHAN BAKAR ALTERNATIF RUMAH TANGGA - Nanang Mudjito (Purifikasi, 2009)
Main problem about study of biogas exploitation for domestic alternative fuel is related to economic value which is directly felt by consumer society. Target of this study is to assist society, mostly of their resident look after ox livestock, in order to exploit potency of livestock dirt to be processed become main fuel becoming domestic requirement. Study of biogas exploitation conducted by compared calor value yielded from three digester that is digester from HILINK UNMER program, Department of Agriculture and Self-Supporting Socialize. Then compared calor value between biogas, kerosene, and firewood. Based the result of economics calor value examination, results that biogas calor is higher if compared with kerosene and firewood. Based on economic calculation results, the consuming of biogas as a main fuel, is more able to thrift economize budget compared than that kerosene and firewood fuel.